Evaluation of the fracture performance of different rubberised bitumens based on the essential work of fracture - Subhy, Ayad; Lo Presti, Davide; Airey, Gordon (Elsevier, 2017)
The fracture performance of rubberised bitumen in addition to one pre-treated with a Warm Mix Additive (Sasobit®) was investigated using different test methods measuring different damage mechanisms. Two Recycled Tyre Rubber (RTR) modifiers together with two base binders were blended in the laboratory to produce various combinations of Recycled Tyre Rubber Modified Bitumens (RTR-MBs). The first RTR is a standard recycled polymer derived from discarded truck and passenger car tyres by ambient grinding. The second RTR consists of 100% recycled truck tyres derived by cryogenic grinding and pre-treated with special oil and WMA to allow further decrease of asphalt mixture production temperatures. A fracture mechanics testing approach was used for evaluating the binder fatigue resistance; consisting of the double-edge-notched tension (DENT) test. The critical tip opening displacement (CTOD) obtained from the DENT test was used for fracture characterization of the binders within the ductile failure region. The study applied the partitioning concept of the total energy of bituminous binders to have a more reliable parameter that could be independent of the stress state of the ligament. The results show that generally the addition of RTR improves the fracture properties of binders indicating better fatigue performance. Pre-treatment with Sasobit® makes the materials more brittle and hence more susceptible to fracture.